Kinematics and Mathematical Modelling of Wheeled Mobile Robots: a compact review - Benjamin Kommey; Owusu-Banahene Banabas Nana Kwame; Nana Owusu Effah; Nathaniel Ato-Sam; Kwame Agyeman-Prempeh (International Journal of Applied Sciences and Smart Technologies, 2026)
This paper presents a comprehensive review on the kinematics and mathematical modelling of wheeled mobile robots. Wheeled mobile robots are a class of robots whose locomotion is facilitated by a set of wheels. The paper delves into the aspects that have proved to be the center of research as far as wheeled mobile robots are concerned, that is, stability, control and path planning. By examining the works in these areas, this paper evaluates the proposed solutions and discusses the findings in various works.